Molecular screening of PROKR2 gene in girls with idiopathic central precocious puberty - Francesca Aiello; Grazia Cirillo; Alessandra Cassio; Raffaella Di Mase; Gianluca Tornese; Giuseppina R. Umano; Emanuele Miraglia del Giudice; Anna Grandone (BMC, 2021)
Abstract Background Prokineticin receptor 2 (PROKR2) loss of function mutations have been described as cause of hypogonadotropic hypogonadism. In 2017, a first case of central precocious puberty (CPP) caused by PROKR2 heterozygous gain of function mutation was described in a 3.5 years-old girl. No other cases have been reported yet. This study performs a molecular screening in girls with early onset CPP (breast budding before 6 years of age) to identify possible alterations in PROKR2. Methods We analysed DNA of 31 girls with idiopathic CPP diagnosed via basal LH levels > 0.3 IU/L or peak-LH > 5 IU/L after stimulation, without any MKRN3 mutations. The Fisher exact test was used to compare polymorphism allele frequency to corresponding ones in genome aggregation database (gnomAD). Results No rare variants were identified. Five polymorphisms were found (rs6076809, rs8116897, rS3746684, rs3746682, rs3746683). All except one (i.e. rs3746682) had a minor allele frequency (MAF) similar to that reported in literature. rs3746682 presented a MAF higher than that described in the gnomAD (0.84 in our cohort vs 0.25 from gnomAD). Conclusions As for other G protein-coupled receptors (i.e. GPR54), mutations in PROKR2 do not seem to be a frequent cause of CPP in girls.